Patients in a Depression Collaborative Care Model of Care - Kurt B. Angstman PhD; Mark D. Williams PhD (SAGE Publishing, 2010)
A collaborative care model (CCM) has been implemented for management of depression. This paper studies the impact that the CCM had on cost measures for the period of six months after initial diagnosis of depression compared to patients receiving usual care (UC). There was a significant increase in the CPT costs for the six months following diagnosis in the CCM group ($451.35 vs. $323.50, P < 0.001). The average CPT cost rank and CPT cost differential were also significantly increased in the CCM group. The adjusted means of the CPT costs were (when controlling for prior utilization) $452.11 for the CCM group and $322.09 for UC (P < 0.001). In the CCM group; there were 161 patients (73.5%) that achieved a clinical response for their depression compared to the UC group, which had a 15.1% (18/119) response rate (P < 0.001). There also was a significant difference between the groups in those who were symptoms free of their depression (PHQ-9 score < 5), with the CCM having 59.4% of the patients symptom-free compared to 10.9% of the UC group (P < 0.001). In this group of patients, CCM is associated with markedly improved clinical outcomes for depression, however with a modest short-term increase in CPT costs.